PENGARUH PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE STUDENT TEAM ACHIEVEMENT DIVISIONS TERHADAP HASIL BELAJAR MATEMATIKA PESERTA DIDIK KELAS VIII MTsN 2 LIMA PULUH KOTA - Isra, Novi (Jurnal Edukasi dan Penelitian Matematika, 2023)
Student outcomes of learning are simply changes in behavior as a learning result. Outcomes in result are the attainment of educational goals for students who participate in the teaching and process of learning. The reality on the ground found that the outcomes of learning mathematics by Class VIII students of MTsN 2 Lima Puluh Kota for the 2022/2023 learning year are still low. The solution that can will be increase outcomes in learning by student in mathematics is to apply the type is model learning in cooperative for student achievement divisions. The research purpose was to give description whether the mathematics learning outcomes of students who studied using the student team achievement divisions cooperative model in learning were better than those who learned by direct learning in class VIII MTsN 2 Lima Puluh Kota. This research type was quasi-experimental with a randomized control-group only design. The research population were students of class VIII MTsN 2 Lima Puluh Kota. The selected for sample was carried out by using technique in random sampling. The instrument used is a mathematics learning achievement test in consist of essay questions. Based on the research in analysis of data results at the real level and P-value = 0.0228 using the U test, we known that the outcomes of learning by students who studied using the type is model learning in cooperative for student achievement divisions were bettermore good than students who studied using the model of learning in direct for class VIII MTsN 2 Lima Puluh Kota.Keywords– Mathematics Learning Outcomes, Student Teams Achievement Divisions, Direct Learning